Promoting community cohesion and dialogue: Navigating the complexities of Permendagri 52/2020 in Saigon Urban Village and Ambawang Raya Village - Zulkarnaen Zulkarnaen; Arifin Arifin; Jumadi Jumadi; Pabali Musa (Community Empowerment, 2024)
The issuance of Home Affairs Ministry Regulation Number 52 of 2020 regarding regional boundaries has resulted in conflicts among residents of Saigon Urban Village, Pontianak City, and Ambawang Raya Village, Kubu Raya Regency. This community service activity aimed to mitigate these conflicts by facilitating dialogue and fostering cooperation between the two parties, as well as mapping out problems and jointly planning programs. The method employed was a Focus Group Discussion (FGD). The results of the community service activities can be considered successful, based on several indicators. Firstly, both parties engaged in intensive dialogue and reached a common understanding. Secondly, a coordination agreement was established between Ambawang Raya Village and Saigon Urban Village, involving mutual cooperation in community service activities, such as PKK (Family Welfare Education) programs. Thirdly, the community has gained a better understanding of the issues arising from the implemented policy.